Organizational Identity and Organizational Identification: A Critical Realist Design Science Perspective. (February 2013) - Hodgkinson, Gerard P.
Scholarly research directed toward the analysis of organizational identity and organizational identification is fragmented along disciplinary and subdisciplinary fault lines that mirror the current intellectual and social organization of the management and organization studies field. Adopting a critical realist design science perspective, the author challenges researchers to set aside their own identity concerns to embark on an ambitious program of work that capitalizes on the strengths of the alternative perspectives in play, with a view to generating insights that are truly greater than the sum of the parts. The imperative for doing so, at this critical juncture, is the need to address the pressing challenges that threaten to harm beyond repair the social harmony that is the bedrock of the world economy and society.